2007
DOI: 10.1172/jci32077
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN innate immune response to adenovirus-mediated IFN-γ gene transfer contributes to the regression of cutaneous lymphomas

Abstract: IntroductionPrimary cutaneous lymphomas (CLs) represent the second most common extranodal group of non-Hodgkin lymphomas and are characterized by an accumulation of clonal T or B lymphocytes preferentially homing to the skin (1). Most CLs are indolent diseases with good prognosis that display a chronic course, sometimes progressing over decades. This in turn creates an increasing need for treatment modalities that would effectively control the disease for a longer time period together with showing good tolerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…Controlled multicenter studies are also required to assess the efficacy of new therapies, such as yttrium-90 ibritumomab tiuxetan (Zevalin) or 131I-tositumomab (Bexxar) radioimmunotherapy 97 and pegylated liposomal doxorubicin 98 (plus rituximab) in PCLBCL, LT and gene therapy with adenovirus-mediated transfer of IFN-␥ in PCFCL and PCMZL. [99][100][101] Today, only the last mentioned approach is investigated in a prospective trial. Finally, patients with a CBCL can best be managed in centers where a close collaboration between dermatologist, hematologist/ oncologist, and radiation oncologist exists.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled multicenter studies are also required to assess the efficacy of new therapies, such as yttrium-90 ibritumomab tiuxetan (Zevalin) or 131I-tositumomab (Bexxar) radioimmunotherapy 97 and pegylated liposomal doxorubicin 98 (plus rituximab) in PCLBCL, LT and gene therapy with adenovirus-mediated transfer of IFN-␥ in PCFCL and PCMZL. [99][100][101] Today, only the last mentioned approach is investigated in a prospective trial. Finally, patients with a CBCL can best be managed in centers where a close collaboration between dermatologist, hematologist/ oncologist, and radiation oncologist exists.…”
Section: Discussionmentioning
confidence: 99%
“…B2M is known as a classic IFN-responsive gene (Yan et al, 2004;Gottenberg et al, 2006;Gray et al, 2006;Joyce et al, 2007;Scherbik et al, 2007;Urosevic et al, 2007). Interferons were originally discovered as antiviral proteins that inhibit virus replication (Isaacs and Lindenmann, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The Ad entry-mediated production of type I IFNs has been recognized only recently. The importance of IFN-αβ production was indicated by clinical trials with oncolytic Ads, where a better prognosis was associated with situations in which recombinant Ad vectors induced robust IFN-αβ responses [104]. While pDCs can recognize Ad DNA via TLR9 in vitro [71,72,80], in vivo studies in Ad-infected mice have shown that the majority of IFN-αβ is produced in myeloid DCs (Fig.…”
Section: Signalling and Cytokine Responses Requiring Ad Endosomal Escapementioning
confidence: 99%